30 years of primary health care reforms in Estonia: The role of financial incentives to achieve a multidisciplinary primary health care system. (April 2023) - Habicht, Triin; Kasekamp, Kaija; Webb, Erin
Highlights: Strengthening primary health care (PHC) has been an Estonian reform priority. The PHC reforms emphasize multidisciplinary care and PHC centres over single providers. To encourage these changes, Estonia has introduced several financial incentives. EU structural funds have been extensively used to fund PHC infrastructure investments. Financial, legal, and workforce challenges to wider PHC reforms still remain. Abstract: Estonia has a legacy of hospital-focused service provision, but since the 1990s, has introduced a series of reforms to strengthen primary health care (PHC). The recent PHC reforms have placed an increasing focus on multidisciplinary care, involving home nurses, midwives, and physiotherapists, and emphasize PHC centres over single physician practices. These incremental reforms, without a supporting legal basis nor explicitly defined timelines and targets, nonetheless demonstrated the ability of financial incentives to drive change. EU structural funds in particular provided essential funding for infrastructure investments in PHC. Yet not all stakeholders supported these initiatives, largely due to the uncertain sustainability of funding. The EHIF also adjusted contract and payment terms to support PHC reforms, with some concessions to PHC providers operating as single practitioners. Despite substantial progress over the last three decades to shift the focus to PHC, there are some important bottlenecks that hinder the progress. These include PHC providers' hesitance to give up their freedom as single practitioners, low interest from specialists to start working at the PHC level, and a lack of financial incentives and adequate funding for a broader scope of PHC services. This looks to become more challenging in the future, as nearly half of family physicians are 60 years old or older. The development of the new PHC strategy in 2023 is very timely to comprehensively address these bottlenecks and to set the vision for the future of PHC in Estonia.